2013
DOI: 10.7314/apjcp.2013.14.9.5199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Hippo Signaling Pathway in Human Gastric Cancer

Abstract: Background/Aim: The Hippo signaling pathway is a newly discovered and conserved signaling cascade, which regulates organ size control by governing cell proliferation and apoptosis. This study aimed to investigate its effects in human gastric cancer. Methods: Tumor tissues (n=60), adjacent non-tumor tissues (n=60) and normal tissues (n=60) were obtained from the same patients with primary gastric cancer (GC). In addition, 70 samples of chronic atrophic gastritis (CAG) tissues were obtained from patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 21 publications
7
63
0
Order By: Relevance
“…We observed a strong decrease of 55.06% (38 of 69) and 66.66% (46 of 69) in LATS1and LATS2 mRNA expression respectively in NSCLC tissues as compared to normal. These results are quite comparable to those observed in NSCLC [24], Soft tissue sarcomas [12], breast cancers [20], astrocytomas [16], gliomas [25] colorectal cancers [26], gastric cancers [27] and ALL [18]. Since, LATS1 is reportedly involved in the control of proliferation, invasion, apoptosis and/or differentiation of various types of cells [28,29] we also compared the LATS1 mRNA expression with various clinicopathological characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We observed a strong decrease of 55.06% (38 of 69) and 66.66% (46 of 69) in LATS1and LATS2 mRNA expression respectively in NSCLC tissues as compared to normal. These results are quite comparable to those observed in NSCLC [24], Soft tissue sarcomas [12], breast cancers [20], astrocytomas [16], gliomas [25] colorectal cancers [26], gastric cancers [27] and ALL [18]. Since, LATS1 is reportedly involved in the control of proliferation, invasion, apoptosis and/or differentiation of various types of cells [28,29] we also compared the LATS1 mRNA expression with various clinicopathological characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…However, in our study, a significant decrease in LATS1 and LATS2 mRNA expression was observed in NSCLC tissues with LATS1 and LATS2 hypermethylation respectively, than those without hypermethylation (P < 0.001) suggesting that hypermethylation of the promoter region down-regulates its expressionand is in consistence with the reports on ALL [18], breast cancers [20], astrocytomas [7], soft tissue sarcomas [12], colorectal cancers [26], and gastric cancers [27], which showed that hypermethylation of LATS1 and LATS2 genes was associated with a decreased mRNA expression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Hippo pathway plays an important role in tumorigenesis and tumor progression through the YAP-TEAD complex [27]. In recent years, the Hippo signaling pathway was shown to be involved in the development, progression, and metastasis of human GC [17,28]. Furthermore, Yap1 exhibits oncogenic activity in cancer via crosstalk with other signaling pathways, such as Wnt, RAF/MEK/ERK, Notch, and PTEN/PI3K/AKT [17,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a study by Kim et al (2013) expressions for stem cell markers including Oct4 were inducible by treatment with H 2 O 2 of the human malignant mesothelial cell line. In a study by Zhou et al (2013) using human biopsy materials of gastric origin, the Hippo signalling pathway marker mRNAs including that of Oct4 exhibited an increasing tendency from cancerous tissue to normal gastric mucosa. And the mRNA expressions had a close correlation with lymphatic metastasis and tumor TNM staging.…”
Section: Discussionmentioning
confidence: 99%